Excessive Erythrocytosis and Chronic Mountain Sickness in Dwellers of the Highest City in the World - Hancco, Ivan; Bailly, Sébastien; Baillieul, Sébastien; Doutreleau, Stéphane; Germain, Michèle; Pépin, Jean-Louis; Verges, Samuel (Frontiers in Physiology, 2020)
Background. While millions of people are living permanently at high altitude (>2500 m) worldwide, the mechanisms underlying their tolerance to chronic hypoxia and those responsible for the occurrence of chronic mountain sickness (CMS) remain to be elucidated. Excessive erythrocytosis (EE) is thought to be the main mechanism responsible for CMS symptoms and is included in the definition of CMS but the precise interplay between EE and symptoms of CMS requires further investigations. Methods. The present study benefits from an exceptional dataset coming from 1594 dwellers of La Rinconada, the highest city in the world (5100-5300 m). Based on individual clinical characteristics, subjects were categorized according to the presence of EE and CMS diagnosis, based on current guidelines. Results. In this population of relatively young (32 [23; 39] years) highlanders residing in La Rinconada for only a few years (3 [2; 5] years), the internal prevalence of EE (44%) was high while the internal prevalence of CMS (14%) was similar compared to previous reports in highlander populations living at lower altitude (4000 m) in the Andes. Individuals with EE reported less symptoms compared to individuals with lower hematocrit values. Multivariable analysis revealed that age and sex are the main factors associated with EE while age, hematocrit and number of years living at La Rinconada are factors associated with CMS symptoms. Conclusion. In this specific population of La Rinconada, high hematocrit values were observed but were associated with limited symptoms. These results raise important questions regarding the definition of EE and CMS and their underlying mechanisms in high-altitude populations.